Waktu Tunggu Pelayanan Resep Pasien Rawat Jalan di Rumah Sakit Umum Kota Tangerang Selatan Tahun 2018 - Humaira Fadhilah; Devi Novita Indriyani; Riris Andriati (STIKes Kharisma Persada, 2019)
One of the pharmaceutical care standard in hospital is waiting time. The prescribed service waiting time is the time period under which the prescription begins to be delivered by the patient to the patient receiving the drug. The purpose of this research is to know the waiting time of prescription service at Pharmaceutical Installation of South Tangerang City General Hospital compared with minimum service standard of Hospital based on Health Minister Decree No. 129 / MenkesSK / II / 2008. This research is descriptive research, the researcher only make observation to prescription service waiting time. The research was conducted in Pharmaceutical Installation RSU South Tangerang City in March 2018. The sample in this research is recipe served from outpatient in march 2018. Sampling technique in this research is total sampling. The sample obtained 129 consisting of 97 non-prescribed recipes and 32 prescription recipes. From this study, the average total waiting time of prescription service was 48.37 minutes for non-prescribed recipes and 173.38 minutes for prescription recipe. The average waiting time for non-prescribed and concocted prescription services did not meet the minimum hospital service standards pursuant to Kepmenkes RI. 129 of 2008.